Inventory of medicinal herbs utilized for the treatment of musculoskeletal disorders in district Kupwara of Jammu and Kashmir - Mir, Tawseef Ahmad; Jan, Muatasim; Bussmann, Rainer W.; Bilal, Tuybia (Ethnobotany Research and Applications, 2022)
Background: The medicinal plants are used for the treatment of various disorders and are believed as a promising agent in the local traditional health care system throughout the globe. This paper provides noteworthy information regarding the use of medicinal herbs for the treatment of musculoskeletal disorders in district Kupwara of Jammu and Kashmir. Methods: Extensive surveys (31 visits) were conducted in the study area during August 2020 to January 2021 for the collection of medicinal plants and the traditional knowledge associated with them. A total of 75 participants were interviewed using group discussions (n=12 with n=6 people each) and semi structured interviews (n=59). Documented ethnomedicinal data was analyzed using quantitative ethnobotanical indices including use value (UV). Results: During the study a total of 45 plants belonging to 20 different families were reported with their medicinal usage to treat musculoskeletal disorders. Asteraceae (13 species) was found to be the dominant family and leaves (41%) were found to be used for the preparation of most of the remedies. Herbs were reported to be the dominant plants utilized with paste as the common method of preparation and topical method as the dominant method of administration. The highest use value (0.49) was reported for Foeniculum vulgare. Conclusion: It can be concluded that, local inhabitants still prioritize herbal medicines as an effective way to treat MSK disorders. This comprehensive investigation helps in phytochemistry and pharmacological research to screen such medicinal plant species for future drug discovery development which give more interesting information with global interest. Scientific authentication of the bio-activity of the particular medicinal plants will validate the integration and use of these natural medications for primary health care of local populations. Keywords: Musculoskeletal disorders, Ethnomedicine, Use value, Kupwara, J&K